The Role of Teacher Pedagogic Competence in Improving Student Learning Achievement in Elementary School - Gustisari, Diantika; Robandi, Babang; Suyitno, Y (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
The learning process and learning outcomes of students are not only determined by the school, patterns, structure and content of the curriculum, but are largely determined by the competence of the teachers who teach and guide them. Policies to improve the quality of education and teaching must always be pursued by various parties, both the government and other components involved in the process. Teachers as one of the components of it have a great task and responsibility, because the future of a nation is determined by qualified teachers. What happens in the field at this time is the lack of teacher's ability to develop subject matter, and the teacher's lack of knowledge about the role and responsibilities at school. Pedagogical competence is expected to improve student learning achievement so that students' learning is at an optimal level. The method used is a survey method. Learning achievement can be seen from the learning outcomes of students who tend to be active and diligent in asking questions in class and can be seen in terms of speaking politely to the teacher. Based on the study results, we concluded that the learning outcomes obtained by students arise from changes in overall behavior